Purchase Intention Produk Halal di Kota Gorontalo - Ali Mohammad (Al-Buhuts, 2022)
This study aims to examine the effect of Product Knowledge and Product Awareness on Purchase Intention of halal products and the effect of the mediating role of Product awareness which can explain the relationship between Product Knowledge and Purchase Intention for halal products. The data needed for the research was collected through an online questionnaire of 87 respondents' responses, using a sampling technique, namely the purposive sampling method with the target respondents being consumers who have used halal products in the city of Gorontalo. The research model and hypotheses between variables were tested using the PLS-SEM method. The results of this study reveal that Product Knowledge has a positive effect on purchase intention of halal products, and Product Awareness has a positive effect on Purchase Intention of halal products, while the Product Awareness effect acts as a partial mediation linking Product Knowledge and Purchase Intention of halal products.